2012
DOI: 10.1161/strokeaha.112.674481
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Hypothermia Is Not Neuroprotective After Severe Hypoxia-Ischemia and Is Deleterious When Delayed by 12 Hours in Neonatal Rats

Abstract: T herapeutic hypothermia (HT) has become standard treatment for term newborns experiencing perinatal asphyxia.1 Randomized controlled trials have shown that HT significantly improves outcome after hypoxia-ischemia (HI). [2][3][4][5][6] Meta-analysis of these suggests that HT improves outcome more in the group with moderate rather than severe HI encephalopathy.7 HI encephalopathy develops during different phases. 8 Initial reperfusion restores cellular energy metabolism in ≈30 to 60 minutes. A latent phase of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
152
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(178 citation statements)
references
References 39 publications
18
152
3
3
Order By: Relevance
“…The hippocampal area loss ratio on the ipsilateral side was calculated as: Hippocampal area loss % = (1−(remaining hippocampal area on the ipsilateral side)/(hippocampal area on the contralateral side)) × 100 A larger brain area loss ratio represents more severe brain injury (7). By using this method, we were able to reliably measure gross morphology change such as cavitations or atrophy.…”
Section: Brain Area Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampal area loss ratio on the ipsilateral side was calculated as: Hippocampal area loss % = (1−(remaining hippocampal area on the ipsilateral side)/(hippocampal area on the contralateral side)) × 100 A larger brain area loss ratio represents more severe brain injury (7). By using this method, we were able to reliably measure gross morphology change such as cavitations or atrophy.…”
Section: Brain Area Lossmentioning
confidence: 99%
“…The recommended clinical HT protocols state that cooling should start within 6 h after birth (3)(4)(5). The effective time window of HT is 5-6 h in both fetal lamb (6) and postnatal day 7 (P7) rats (7) and <3 h in injured newborn pigs (8). In NE infants, better motor outcome has been found at 18 mo if cooling was started within 3 h as compared to those were cooled between 3-6 h of age (9).…”
mentioning
confidence: 99%
“…These conflicting results may not be oppositional considering the possibility that delayed hypothermia may be protective only with milder insults. We consider that the OGD used in this study involves a moderate to severe insult and it is possible that a less severe insult would be compatible with a protective effect of delayed hypothermia as recently demonstrated in a neonatal rat model of hypoxia ischemia (Sabir et al, 2012). As in the Sabir study, delayed hypothermia, or profound hypothermia, increased rather than prevented postischemic injury, which is a clinical concern.…”
Section: Delayed Application Of Hypothermia Can Be Detrimental After mentioning
confidence: 82%
“…We used an organotypic culture model of the developing rat hippocampus that is sensitive to hypothermia protection and damage Warren et al, 2012) A recent study in intact rats showed that when hypothermia postcerebral ischemia was delayed by 3 hours or more, it was not protective or added to injury (Sabir et al, 2012), so we also examined the effects of delaying hypothermia on outcome after OGD. We examined temperatures of 32°C, 23°C, 17°C, and 4°C to span both the therapeutic and potentially injurious range of temperatures, applying hypothermia either immediately after or after a delay from simulated ischemia.…”
mentioning
confidence: 99%
“…A sikeres kezelés-hez mindenképpen szükség van a szülészeti intézmény, a neonatalis transzportért felelős mentőszolgálat és az asphyxiacentrumok közötti jó együttműködésre, hogy a hypothermiás kezelés elérhető legyen akár már a neonatalis transzport során is. Állatkísérletes eredmények és újszülötteken végzett klinikai vizsgálatok alapján ugyanis igazolódott, hogy a terápiás hűtés hatékonysága növel-hető a hypothermia mihamarabbi megkezdésével [28][29][30][31]. A harmadik életórán belül elkezdett terápia tovább fokozza a neuroprotekciót és javítja a hosszú távú kimenetelt a 3-6. életórában megkezdett hűtéshez képest [30].…”
Section: Megbeszélésunclassified